Parasutterella, in association with irritable bowel syndrome and intestinal chronic inflammation - Chen, Yan‐Jie; Wu, Hao; Wu, Sheng‐Di; Lu, Nan; Wang, Yi‐Ting; Liu, Hai‐Ning; Dong, Ling; Liu, Tao‐Tao; Shen, Xi‐Zhong (Journal of gastroenterology and hepatology, 2018)
Background and Aim Irritable bowel syndrome (IBS) is a highly prevalent chronic functional gastrointestinal disorder. Recent studies have showed increasing important role of gut microbiota in the pathophysiological changes of IBS. Our study aims to elaborate the association between intestinal flora with the genesis and the development of IBS. Methods Illumina high‐throughput sequencing technology was applied to investigate microbial communities of IBS patients and healthy donors. Stool specimens from the IBS‐D patients were equally premixed and implanted into germ free C57B/6 mice to construct IBS animal model, and the normal group was also transplanted with normal premixed feces. The post‐transplant defecation and intra‐epithelial lymphocyte counts were evaluated. Microbial communities were also checked by the illumina high‐throughput sequencing technology. Results Fifteen genuses significantly different were found expressed in the gut flora of IBS patients, and six genuses showed significantly different abundances between the stool specimens of mice of IBS group and normal group. Among these differences, Parasutterella expression was remarkably different in both screening and validation experiments and also related to chronic intestinal inflammation; therefore, Parasutterella expression is considered in association with the development and progression of IBS. Conclusion Parasutterella may be related with the genesis and development of IBS and also associated with chronic intestinal inflammation in IBS patients.